2009
DOI: 10.1590/s1807-59322009000500011
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Red Wine Consumption Promotes Differential Effects on Plasma Levels of High-Density Lipoprotein Cholesterol, Sympathetic Activity, and Endothelial Function in Hypercholesterolemic, Hypertensive, and Healthy Subjects

Abstract: Andrade ACM, Cesena FHY, Consolim-Colombo FM, Coimbra SR, Benjó AM, Krieger EM, et al. Short-term red wine consumption promotes differential effects on plasma levels of high-density lipoprotein cholesterol, sympathetic activity, and endothelial function in hypercholesterolemic, hypertensive, and healthy subjects. Clinics. 2009;64(5):435-42. OBJECTIVES:To compare the metabolic, hemodynamic, autonomic, and endothelial responses to short-term red wine consumption in subjects with hypercholesterolemia or arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…7 In our previous interventional study, we observed a 21% significant increase in TG levels after short-term red wine intake. 8 However, to the best of our knowledge, it is not known whether and which clinical features influence the increase in TG levels induced by alcoholic drinks. In this regard, our data provide new information suggesting that the variation in plasma TG levels after short-term red wine consumption might be partially dependent on the baseline BMI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 In our previous interventional study, we observed a 21% significant increase in TG levels after short-term red wine intake. 8 However, to the best of our knowledge, it is not known whether and which clinical features influence the increase in TG levels induced by alcoholic drinks. In this regard, our data provide new information suggesting that the variation in plasma TG levels after short-term red wine consumption might be partially dependent on the baseline BMI.…”
Section: Discussionmentioning
confidence: 99%
“…More details on inclusion and exclusion criteria can be found elsewhere. 8,15 Subjects were encouraged not to change their daily dietary habits and physical activity level during the study. Indeed, they were interviewed before and after the experiment, and no significant change in diet or exercise was observed.…”
Section: Study Population and Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that ApoE lipoproteins participate in some way in the processing of APP, perhaps by modulating APP secretases, and may also play a role in the assembly of the neuronal cytoskeleton. High cholesterol levels during mid-life increase the risk of Alzheimer's disease and lipid-lowering therapies including the consumption of wine-derived phenolic compounds can lower this risk which may accordingly lower the risk of developing Alzheimer's disease [140][141][142].…”
Section: Amyloid-β and Apoe-epsilon 4 Allelementioning
confidence: 99%